Patterns of drug combinations used by men who have sex with men in Brazil - Rodrigo Nikobin; Julio Mella-Cobas; Maria Amelia Veras; Francisco Inácio Bastos; Jordi Casabona Barbarà; Valeria Stuardo Ávila; Dartiu Xavier da Silveira (Brazilian Journal of Psychiatry)
Objective: The practice of using drugs to modulate experiences is a well-documented phenomenon worldwide, particularly among men who have sex with men (MSM). This study aims to describe patterns of drug combinations used by Brazilian MSM, embracing a detailed examination of the Brazilian context, which may inspire research elsewhere while enriching the global panorama on MSM drug use. By focusing on Brazilian MSM, the study sheds light on specific drug use combinations, which may help in the development of effective, culturally sensitive public health strategies. Methods: This investigation was conducted within the Latin American MSM Internet Survey, a pioneer online study addressing psychosocial and sexual health of MSM in the region. Conducted from January to May 2018, the survey garnered responses from over 18,139 Brazilian MSM. Using exploratory factor analysis through maximum likelihood estimation, the study identified distinct sub-groups of drug users among 15,499 participants after exclusion due to discrepant responses (Kaiser-Meyer-Olkin measure = 0.94 and Bartlett’s test ≤ 0.01), indicating adequate sampling and suitability for factor analysis across all substances. Results: The factor analysis revealed four primary drug combination groups among participants: Group One (Heavy Drug Users), Group Two (Party Drug Users), Group Three (Conservative Users), and Group Four (Classic Chemsex Users). Each group represents unique drug use patterns and preferences, from the use of potent stimulants to more socially accepted substances like tobacco and cannabis. Notably, Group One, identified as “heavy” drugs users, used particularly risky substances, including mephedrone, crack, crystal meth, heroin, and other synthetic stimulants. Conclusion: The findings reveal diverse and complex drug use patterns among MSM in Brazil. Understanding these patterns is essential for developing targeted interventions and support mechanisms for various sub-groups among MSM. Future research should focus on the health outcomes associated with these patterns and the social and psychological contexts of drug use.